Metode An-Nadhliyah untuk Melatih Bacaan al-Qur’an - Eka Wahyu Hidayati (Academia Publication, 2021)
A phenomenon of Qur'anic education that is faced with a more difficult time where today is easily found in schools where in this education does not use a method but only uses daily methods in reading the Qur'an. In this case it takes a method to facilitate a learning to read the Qur'an. One of them is by using the An-Nahdliyah method, which aims to practice the recitation of the Qur'an properly and correctly. This research uses a type of library research or literature study. The final analysis results use descriptive analytical methods to present about the An-Nahdliyah method in the learning activities of the Qur'an. Thus the researcher formulated the problem: 1) How the reading system in the An-Nahdliyah method, 2) How the teaching and learning process at TPQ An-Nahdliyah. The results obtained as follows: The reading system of The An-Nahdliyah method, including: Tartil, Tahqiq, and Taqhonni. While the educational methods used in the teaching and learning process at TPQ An-Nahdliyah are: demonstration method, drill method, question and answer method, and lecture method..